Additional dydrogesterone for the treatment of chronic endometritis treated with antibiotic in premenopausal women with endometrial polyps: a retrospective cohort study - Yue Liu; Xin Yu; Jing Huang; Chengchao Du; Honggui Zhou; Yamei Yang; Dacheng Qu (BMC, 2022)
Abstract Background To assess the efficacy of dysdrogesterone in the treatment of chronic endometritis (CE) treated with antibiotic in premenopausal women with endometrial polyps (EPs). Methods Routine detection of endometrium was simultaneously conducted to determine whether there was CE by syndecan-1 (CD138), while women underwent hysteroscopic polypectomy in our hospital. Antibiotic was given for the treatment of CE. A total of 235 premenopausal women with CE who underwent hysteroscopic polypectomy were enrolled in the retrospective observational study. In the control group, single antibiotic was given for the treatment of CE form January 2016 to December 2018, and in the treatment group additional dydrogesterone was used from January 2019 to November 2020. Comparison of cure rates of CE with different treatment regimens was performed. Results The cure rates of CE in dydrogesterone and antibiotic combination group and the single antibiotic group were 85.2% and 74.3%, respectively, with overall cure rate of 80.0% (188/235). The combination group showed better effects regarding the cure rate of CE (P < .05). Multivariate analysis confirmed that the cure rate of CE was not affected by age, body mass index, number of EPs, the status of estrogen receptor and the status of progesterone receptor. Conversely, dydrogesterone and endometrial scratching were beneficial factors for cure rate increase with antibiotic treatment. Conclusion Combination of dydrogesterone and antibiotic was more effective for cure rate of CE than antibiotic alone in premenopausal women after hysteroscopic polypectomy. Endometrial scratching also contributed to the cure rate increase with antibiotic treatment.